2001
DOI: 10.1067/mhn.2001.111602
|View full text |Cite
|
Sign up to set email alerts
|

Allergy Testing and Immunotherapy in an Academic Otolaryngology Practice: A 20‐year Review

Abstract: The otolaryngologist-head and neck surgeon is uniquely qualified to perform comprehensive medical and surgical management for patients with complex disease processes involving a component of allergy. We believe that an integrated approach to allergy within an otolaryngology practice optimizes the treatment of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 11 publications
(20 reference statements)
2
22
1
Order By: Relevance
“…We can estimate, however, that 80% of patients who are identified as having allergies by a physician will have a positive allergy skin test. 22,23 Furthermore, the number of affected participants in our dataset is consistent with the 2002 Chartbook on Trends in the Health of Americans, 18 which found that in patients ages 45 to 64 the prevalence of hay fever was 10.8%.…”
Section: Discussionsupporting
confidence: 69%
“…We can estimate, however, that 80% of patients who are identified as having allergies by a physician will have a positive allergy skin test. 22,23 Furthermore, the number of affected participants in our dataset is consistent with the 2002 Chartbook on Trends in the Health of Americans, 18 which found that in patients ages 45 to 64 the prevalence of hay fever was 10.8%.…”
Section: Discussionsupporting
confidence: 69%
“…Loratadine, as an adjunctive therapy of atopic patients with acute sinusitis, was found to modestly improve sneezing and nasal obstruction (2115). It is also noteworthy to mention that half of the allergic patients with a history of sinus surgery and undergoing immunotherapy believed that surgery alone was not sufficient to completely resolve the recurrent episodes of infection related to their sinus disease (2116). Well-conducted clinical trials showing beneficial effects of oral H 1 -antihistamines in patients with CRS are lacking.…”
Section: Rhinosinusitismentioning
confidence: 99%
“…(58,59) Strong correlation between the extent of disease on CT evaluation and the amount of eosinophils within the sinus tissue, as well as the presence of specific IgE antibodies (60) CT changes in patients with ragweed allergy (61) Increased percentage of NP in allergic patients (62) Immunotherapy increases success of surgery (31,63) especially in AFRS (64) Experimental study where nasal challenge with allergen has resulted in secondary maxillary sinus inflammation (26) Possible selection or referral bias (19)(20)(21)(22)(23) No increased percentage of allergy in NP patients (59,(65)(66)(67)(68)(69) Allergic rhinitis was less prevalent in those with worse disease on sinus CT scans (56) No increase of CRS during pollen season (27) The presence of allergy does not affect symptom severity, surgery likelihood, extent of disease on CT (33)(34)(35) Pediatric literature Increased incidence of atopic predisposition in pediatric patients with sinusitis (70, 71) Correlation of allergy and severity of sinus disease (70,72) ESS in children with AR does not have a poorer outcome. Treatment for the allergy before surgery may improve the success of ESS (73) Same percentage of positive allergy test in CRS and normal children (74) Same prevalence of CRS in atopic and nonatopic children (75) Percentage of opacification the same between allergic and nonallergic adults and children (76) ESS, endoscopic sinus surgery; AFRS, allergic fungal rhinosinusitis; AR, allergic rhinitis; CRS, chronic rhinosinusitis; NP, nasal polyps.…”
Section: Conflicts Of Interestmentioning
confidence: 99%